Program Pendidikan Kesetaraan Pondok Pesantren Salafiyah (PKPPS) di Ma’had Zaadul Ma’ad Palembang - Robin Andespa; Fajri Ismail; Mardel Mardeli (Studia Manageria, 2021)
This study aims to evaluate the Equality Education program at the Salafiyah Islamic Boarding School (PKPPS). The research was conducted in Ma'had Zaadul Ma'ad Palembang. The research time starts from October 2020 to April 2021. The research subjects are students of the Salafiyah Wustha level. This type of research is an evaluation research using the CIPP evaluation model (context, input, process, product). Evaluation is carried out to see the level of conformity of program implementation with the criteria set out in the PKPPS Technical Guidelines. The results showed that the PKPPS program at the Salafiyah Wustha level in terms of the context, process, or product dimensions was in accordance with the criteria so that the program needed to be continued. However, if viewed from the input dimension, it only reached a sufficient level of conformity. The researcher's recommendation for policy makers is to limit a maximum of 30 students per study group, educators who have not received a bachelor's degree to be directed to continue their education, educators are expected to teach subjects according to academic qualifications, the need for infrastructure is not fulfilled, and damaged infrastructure needs to be repaired. The components of the Salafiyah Wustha PKPPS program that need to be disseminated are mainly related to increasing the number of students, namely a distinctive vision and mission, the establishment of programs based on community needs, and the use of online media in the study of the Kitab Kuning.